CONSUMER SATISFACTION INDEX OF FAMILY PLANNING COUNSELORS’ PERFORMANCE IN WEST JAVA PROVINCE - Suhenda, Dadang; Hutasoit, Evalina Franciska; Ghani, Mochammad Wahyu; Erti, Erti; Nuraini, Nuraini (Universitas Airlangga, 2024)
Family planning counselors or Penyuluh Keluarga Berencana (PKB) are frontline implementers of the population, family planning, and family development program at the grassroots level. This study aims to know the consumer satisfaction index of the PKB performance of The National Population and Family Planning Board or Badan Kependudukan dan Keluarga Berencana (BKKBN) representative of West Java. The consumer satisfaction index was measured using the Permenpan RI (Regulation of the Minister for Administrative Reform and Bureaucratic Reform of the Republic of Indonesia) Number 14 (2017). The study method is descriptive comparative through a purposive sampling survey using a 9 Likert scale. Based on the study, it is shown that the consumer satisfaction index of the PKB performance in 2018 is 71,89, which is service quality category C, which means underperformance. Based on the service, the timing of service is the lowest index, as much as 0.29, and the average of 2.64. PKB does not utilize the time for counseling and post-service assistance well or tends to be slow. Out of 10 steps of PKB, only 2 indicators are measured as satisfactory, which is the formal figure approach and the monitoring and evaluation of the record and reporting (RR). Hence, it is recommended that the BKKBN to maintain the PKB performance through training and development continually, a guidelines book, and periodic training of the 10 PKB steps, as well as the mapping of the affordability to reach PKB service.